PERANCANGAN SISTEM INFORMASI WEDDING ORGANIZER BERBASIS WEB PADA NIKAH YUK ORGANIZE - Daffa Kinciano Putra (2023)
A wedding organizer (WO) is a special service that assists the bride and groom and their families in planning and supervising the implementation of a series of wedding events according to a predetermined schedule. Wedding organizer (WO) Nikah Yuk Organize has a problem, namely repeated questions from each customer starting from the packages available, to the package prices provided, this is due to a lack of information regarding prices and pictures of the wedding packages provided, Therefore the right solution to the problem that occurs is to create a website-based wedding organize information system that is connected to the internet. In the development of this information technology using the waterfall strategy method where the manufacturing process is structured and sequential starting from analysis, design, coding & testing, implementation, and maintenance.